THE EFFECT OF FINANCIAL PERFORMANCE ON THE VALUE OF THE COMPANY WITH DIVIDEND POLICY AS A MODERATION VARIABLE IN PHARMACY COMPANIES LISTED ON THE IDX - Adbel Twosheila Mosa Buciarda; Ira Wikartika (PT FORMOSA CENDEKIA GLOBAL, 2024)
The increase in demand for supplements, vitamins and herbal medicines that function to increase endurance during a pandemic in general has made pharmaceutical companies experience a significant increase in profits. The purpose of this study was to determine the effect of financial performance with indicators of profitability, leverage, and liquidity on firm value with dividend policy as a moderating variable. The method used in this research is purposive sampling by using several criteria to obtain research samples. The analysis used in this research is Moderated Regression Analysis (MRA) with the help of using the SPSS application. The results obtained are that simultaneously the variables of profitability, leverage, liquidity, and dividend policy affect firm value. Partially, profitability can make a contribution and significant effect on firm value, leverage and liquidity cannot make a contribution and significant effect on firm value. In addition, dividend policy can moderate profitability, leverage, and liquidity on firm value.